Produktivní kultura vyučování a učení v didaktických kazuistikách - Janík, Tomáš (Pedagogický výzkum v teorii a praxi, 2022)
Title in English: Productive culture of teaching and learning in didactic case studies The book introduces the issue of productive culture of teaching and learning in broader didactical context. In the first part of the book, three areas of productive culture of teaching and learning are as theoretical framework presented: 1. clarity, structure, coherence, 2. cognitive activation, instrumentalization, semantization, 3. Supportive learning environment. The second part of the book presents 17 didactic case studies that have been developed by teams that consisted of researchers and teachers from schools. The aim of didactic case studies is to highlight key areas of productive culture of teaching and learning.